Combined Interventions for Severe Novel Coronavirus Disease (COVID-19): Experience from 350 Patients - Guo T; Shen Q; Zhou Z; Li J; Guo W; He W; Wang Y; Xiang Z; Huang P; Zeng N; Qin Q; Chen P; et al. (Infection and Drug Resistance, 2020)
Ting Guo,1– 3,* Qinxue Shen,1– 3,* Zhiguo Zhou,4 Jinhua Li,1– 3 Wei Guo,1– 3 Wenlong He,1– 3 Yunnian Wang,5 Zhi Xiang,6 Peng Huang,7 Nanyang Zeng,8 Qingwu Qin,1– 3 Ping Chen,1– 3 Hong Luo,1– 3 Hong Peng1– 3 1Department of Respiratory and Critical Care Medicine, The Second Xiangya Hospital of Central-South University, Changsha, Hunan, People’s Republic of China; 2Research Unit of Respiratory Disease, Central-South University, Changsha, Hunan, People’s Republic of China; 3The Respiratory Disease Diagnosis and Treatment Center of Hunan Province, Changsha, Hunan, People’s Republic of China; 4Department of Respiratory and Critical Care Medicine, The First Hospital of Changsha, Changsha, Hunan, People’s Republic of China; 5Department of Respiratory and Critical Care Medicine, The Traditional Chinese Medicine Hospital of Liling, Zhuzhou, Hunan, People’s Republic of China; 6Department of Respiratory and Critical Care Medicine, The First People’s Hospital of Huaihua, Huaihua, Hunan, People’s Republic of China; 7Department of Respiratory and Critical Care Medicine, The Central Hospital of Zhuzhou, Zhuzhou, Hunan, People’s Republic of China; 8Department of Infectious Disease, The Lvkou People’s Hospital of Zhuzhou, Zhuzhou, Hunan, People’s Republic of China*These authors contributed equally to this workCorrespondence: Hong PengDepartment of Respiratory and Critical Care Medicine, The Second Xiangya Hospital of Central-South University, No. 139 Renmin Middle Road, Changsha, Hunan 410011, People’s Republic of ChinaTel +86 13807494486Email penghong66@csu.edu.cnPurpose: To summarize the clinical features and effective therapy of severe COVID-19 patients.Patients and Methods: In this retrospective, multicenter study, the medical records of COVID-19 patients in Hunan, from January 21, 2020 to February 19, 2020 were reviewed.Results: Of the 350 COVID-19 patients, 13.7% were severe cases. On admission, compared with non-severe patients, more severe patients had a neutrophil/lymphocyte ratio > 3 (58.3% vs 33.8%, P=0.001), D-dimer > 1 mg/L (41.7% vs 13.6%, P< 0.0001), higher level of CRP (39.1 mg/L, IQR18.1– 75.9 vs 13.4 mg/L, IQR5.0– 32.8, P< 0.0001), and multiple pneumonia on CT (77.1% vs 18.2%, P< 0.0001). All severe patients received oxygen support. 95.8% of them received antivirals, and the most frequent therapy was lopinavir and ritonavir plus human interferon-α 2b. Moxifloxacin was used in 70.8% severe patients. The total dosage of methylprednisolone sodium succinate was 640 mg (IQR 360– 960) in severe patients, and the duration of use was 8.5 days (IQR 6.8– 11.3). The total dosage of immunoglobulin was 80 g (IQR, 60– 140) in severe patients, and the duration was 8.0 days (IQR, 6.0– 11.5). As of March 15, 2020, 95.8% of the severe patients had been discharged and only two deaths occurred.Conclusion: The rate of severe cases and mortality of COVID-19 in Hunan are lower than those in Wuhan. In addition to antivirals and oxygen support, timely interventions including corticosteroids, immunoglobulin, and antibiotics, contribute to improving the prognosis of severe COVID-19 patients.Keywords: coronavirus disease 2019, SARS-CoV-2, severe disease, corticosteroid, immunoglobulin